Reducing CO2 emissions in a typical 60 years old detached house in London - Barbhuiya, S.; Barbhuiya, Salim (College Publishing, 2013)
In this paper an attempt has been made to provide the best options for renewable energy and low carbon technologies to reduce CO2 emissions from a detached house built in1950 located in London. The options for energy efficiency measures—photovoltaic, solar thermal, wind turbine, ground source heat pump, Gas CHP—have been evaluated on the basis of energy and CO2 savings and technical viability. The main conclusions derived from this study are summarised in this paper.